The combination effect of Naphthalene Acetic Acid (NAA) and Benzyl Amino Purine (BAP) in micro propagation of castrol oil plant (Jatropha curcas L.) - Meutia Zahara; Zairin Thomy; Essy Harnelly (Syiah Kuala University, 2011)
The fossil energy reservation decreases day by day, this situation impacted to the energy crises especially fuel energy which is increasing in the price on over the world. The scientists/researchers are trying to develop the renewable energy (renewable fuel) as the energy alternative, one of these called biodiesel. Taking the benefit from Jatropha curcas’ seed as raw material for the fuel is one of the alternative ways to reduce the fuel demand and also can save the countries’ foreign exchange. J. curcas’ oil is renewable fuel and non edible oil, so that it will not compete with oil consumption, such as palm oil, corn oil, etc. The combination between Naphthalene acetic acid (NAA) (1- 2 ppm) and Benzyl Amino Purine (BAP) (0,5 and 1 ppm) for micro propagation of Castrol oil plant (Jatropha curcas L.) was tried to induce the callus formation by using the meristem shoot as the explants. The result showed that the combination of NAA 1.5 ppm and BAP 0,5 ppm gave the best result for the callus formation.